Infectious bursal disease virus tissue tropism and pathogenesis of the infection in chickens by application of in situ PCR, immunoperoxase and HE staining - Elawad, Hussein Abdallah; Bejo, Mohd Hair; Liew, Pit Sze; Adamu, Lawan; Omar, Abdul Rahman; Arshad, Siti Suri; Mohammed, Majed H.; Ideris, Aini (Academic Press, 2019)
Infectious bursal disease is one of an OIE list of notifiable diseases. Chicken is the only host that manifests clinicalsigns and its pathogenicity is correlated with the distribution of antigens in organs. This study was conducted todetermine disease pathogenesis and virus tissue tropism byin situPCR, immunoperoxidase staining (IPS), and HEstaining. Twenty four chickens were infected with very virulent Infectious Bursal Disease Virus (vvIBDV). Fifteenchickens were kept as a control group. Infected chickens were sacrificed at hrs 2, 4, 6, 12, days 1, 2, 4, and 6post-inoculation (pi). While, control chickens were euthanized on days 0, 1, 2, 4, and 6 pi. Different tissues werecollected,fixed in 10% buffered formalin, and processed. At hr 2 pi, virus was detected in intestinal, junction ofthe proventriculus and gizzard, cecal tonsil, liver, kidney, and bursa of Fabricius. At hr 4 pi, virus reached spleen,and at hr 6 pi, it entered thymus. At hr 12 pi, virus concentration increased in positive tissues. The latest invadedtissue was muscle on day 1 pi. Secondary viraemia occurred during 12–24 h pi.In situPCR was the most sensitivetechnique to highlight obscure points of infection in this study.